The Authorship Guestion of The Yotvingian Book - Kregždys, Rolandas (Knygotyra, 2019)
In this article, one of the most important sources of Baltic mythology of the 16th century – The Yotvingian Book – is analyzed: the possible circumstances of its creation, purpose, dating, and the problems of authorship are described.The written source, also called by its original title Der vnglaubigen // Sudauen ihrer bockheiligung mit sambt andern Ceremonien, so sie tzu brauchen gepflegeth, is a conventional, probably the most exhaustive, and the most important description of the ethnocultural tradition of the tribe that spoke Yotvingian, one of the two languages of Western Balts, recorded during the Reformation period. It is based on the source of information disseminated in several variants of manuscripts, and later in small printed books (reprints).The Yotvingian Book has been repeatedly discussed by many art workers of different epochs and branches of science. The dating and its possible authorship were differently interpreted. The most valuable analysis was carried out by W. Mannhardt. It was very essentially supplemented by the Lithuanian scientist I. Lukšaitė. Based on the hypotheses advanced by her, it is possible, and necessary, to once again reconsider the known facts, the actual material, and the structural typology of the source. Therefore, the purpose of this article was a study of the above issues.In this article, the question of the meaning of the latent acrostics is addressed anew. They are found in the Bible, in extrabiblical sources, and in ancient Eastern literature. There are various explanations for the phenomenon, and in each case, the function of the acrostic should be determined through a comprehensive analysis of the composition itself.It is highly believable that the author of The Yotvingian Book concealed the latent message. It is to be assumed that his personal name of Semitic origin is encoded in the catalogue of theonyms of The Yotvingian Book. The name is composed using the numerological system of Gematria in accordance with the alphanumeric code of M.-Hebr. mispār heḵǝraẖi combining it with the AvGag alphabetic sequences (i.e., partly replacing each letter with the next one): Ishmǝrai Sābā bēn Āḏām, i.e., Ishmerai Saba, Adam’s son. The surname M.-Hebr. Sābā (“an old man; a man with grey hair”) is a synonym to the G. Graumann “ditto” and Gr. Πολιανδρος “ditto.” These surnames indicate the author of The Yotvingian Book – Johannes Poliander, or Johann Graumann. He was a German pastor, theologian, teacher, humanist, reformer, and Lutheran leader.Based on the results of the analysis (cf. the list of theonyms of The Yotvingian Book which presupposes a reconstruction of the demonological order of the mythonyms), it is possible to make the statement that The Yotvingian Book should not be regarded as a material of the Episcopal inspection (therefore, it should not be related with Agenda Ecclesiastica or its authors) or an odd fragment of a more extensive source written adhering to the stylistics of the Renaissance, but as an example of a juristic document. Therefore, it cannot be characterized as an authentic source of the religious practices and beliefs of Western Balts.
Keywords: The Yotvingian Book; Johannes Poliander; latent acrostic; Gematria